Communication in palliative care: Results: from a mixed-methods study in Italian-speaking Switzerland: Presenter(s): Nicaola Diviani, Swiss Paraplegic Research / University of Lucerne, Switzerland. (April 2023) - Bennardi, Marco; Gamondi, Claudia; Saletti, Piercarlo; Stüssi, Georg; Rubinelli, Sara
Abstract : Background: Palliative care services hold a great potential to improve the quality of life of patients suffering from chronic degenerative diseases and their families. Their utilization, however, is not yet optimal, even in high-resource countries, and not all those who might benefit from palliative care have access to its services. The international literature suggests that among the possible reasons for the underutilization are problems at the level of communication, both among healthcare professionals and the public. This study, focusing on cancer, aims to explore this aspect further and identify possible communication-related barriers and facilitators to the use of palliative care services in Italian-speaking Switzerland. Methods: A mixed-methods approach was chosen. Qualitative and quantitative data were collected between 2017 and 2020 through in-depth interviews with healthcare professionals (in oncology, palliative care, and primary care), key informants, patients, and their families (N = 50), and through a representative population survey (N = 313). Findings: Our Findings: allowed us to isolate the lack of knowledge about palliative care, its tools, and its benefits as one of the main obstacles to realizing its full potential. Among health professionals, this consists of a lack of mutual knowledge about the work of the different actors, which hurts the quality of collaboration. On the other hand, misconceptions and false beliefs about palliative care in the population are associated with negative attitudes towards palliative care and a reluctance to address the issue with formal and informal caregivers. Discussion: In an effort to foster the utilization of palliative care services, targeted educational communication interventions are needed both to promote the interprofessional and inter-disciplinary collaboration between the different health professionals involved in palliative care and to increase awareness and knowledge of palliative care services in the population.